Stability Analysis of SIQS Mathematical Model for Pandemic Coronavirus Spread - Verma, Vinay (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we approach conceptual mathematical models for COVID-19 eruption and it's abstinence metering; quarantine. In this circumstance, mathematical models are a grandly tool to make use of an impressive strategy in order to fight against this pandemic. We define the positivity, boundedness of solutions and basic reproduction number. Then, we study local and global stability analysis of equilibrium to examine its epidemiological relevance. Our model represent the various transmission route in the infection dynamics, and diligence the role of the environmental reservoir in the transmission and dispersion of this disease. Simulation explication of the model ratify to the analytical results.